2021
DOI: 10.3390/v13091765
|View full text |Cite
|
Sign up to set email alerts
|

DDX21, a Host Restriction Factor of FMDV IRES-Dependent Translation and Replication

Abstract: In cells, the contributions of DEAD-box helicases (DDXs), without which cellular life is impossible, are of utmost importance. The extremely diverse roles of the nucleolar helicase DDX21, ranging from fundamental cellular processes such as cell growth, ribosome biogenesis, protein translation, protein–protein interaction, mediating and sensing transcription, and gene regulation to viral manipulation, drew our attention. We designed this project to study virus–host interactions and viral pathogenesis. A pulldow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 88 publications
1
20
0
Order By: Relevance
“…DDX21 was first identified as a nucleolar RNA helicase involved in rRNA processing and RNA unwinding [ 42 , 58 ]. However, increasingly more evidence has shown that virus infection or treatment with stimulants, such as poly (I: C) and 3p-hpRNA, promote the translocation of DDX21 from the nucleus to the cytoplasm [ 28 , 41 , 61 ]. Although the exact mechanism of how pDDX21 translocation influences PRRSV replication is not clear, given that DDX21 possesses G-quadruplex-unwinding activity [ 25 ], we speculate that pDDX21 may unwind the viral genome.…”
Section: Discussionmentioning
confidence: 99%
“…DDX21 was first identified as a nucleolar RNA helicase involved in rRNA processing and RNA unwinding [ 42 , 58 ]. However, increasingly more evidence has shown that virus infection or treatment with stimulants, such as poly (I: C) and 3p-hpRNA, promote the translocation of DDX21 from the nucleus to the cytoplasm [ 28 , 41 , 61 ]. Although the exact mechanism of how pDDX21 translocation influences PRRSV replication is not clear, given that DDX21 possesses G-quadruplex-unwinding activity [ 25 ], we speculate that pDDX21 may unwind the viral genome.…”
Section: Discussionmentioning
confidence: 99%
“…DDX60 is not the only DExD/H box RNA helicase observed to inhibit viral IRES-mediated translation. The DEAD box helicase DDX21 was recently shown to antagonize FMDV IRES, and the HCV like IRESs of classical swine fever virus and Seneca Valley virus (Abdullah et al, 2021). However, unlike DDX60, DDX21 is thought to inhibit these IRESs indirectly through upregulation of IFN-ß and IL-8 mRNAs (Abdullah et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The DEAD box helicase DDX21 was recently shown to antagonize FMDV IRES, and the HCV like IRESs of classical swine fever virus and Seneca Valley virus (Abdullah et al, 2021). However, unlike DDX60, DDX21 is thought to inhibit these IRESs indirectly through upregulation of IFN-ß and IL-8 mRNAs (Abdullah et al, 2021). Likewise, the ability for DDX21 to selectively inhibit IRES-mediated translation has not been tested.…”
Section: Discussionmentioning
confidence: 99%
“…All of them have RNA binding activity and some of them also take active part in immune regulation. For instance, DDX21, an RNA helicase, acts in innate immune response as positive regulator of NF-kB signaling ( Zhang et al, 2011 ; Chen et al, 2014 ; Abdullah et al, 2021 ) and as antiviral factor ( Chen et al, 2014 ). In addition, many RBPs commonly targeted by the three viruses are associated with ubiquitin mediated protein degradation pathways (e.g., RPS7, RPL11, RPS2, RPL5) and regulation of apoptotic processes (e.g., SERBP1, RSL1D1, RPS7), thus underlying the key role of RBPs in virus-host interactions.…”
Section: Viral-host Interactomes Of the Emerging Viruses: Commonaliti...mentioning
confidence: 99%